Occurrence and sources of polycyclic aromatic hydrocarbons in atmosphere and soil from 2013 to 2019 in the Fildes Peninsula, Antarctica. (July 2020) - Na, Guangshui; Gao, Yunze; Li, Ruijing; Gao, Hui; Hou, Chao; Ye, Jiandong; Jin, Shuaichen; Zhang, Zhifeng
Abstract: Long-term monitoring is essential for revealing pollution trends, but relevant studies in the Antarctic remain limited. In this study, a seven-year continuous monitoring of polycyclic aromatic hydrocarbons (PAHs) in the atmosphere and soil was carried out at the Fildes Peninsula, Antarctica. Average concentrations of Σ15 PAHs were 7134.491 pg/m 3 and 61.093 ng/g in air and soil, respectively. A declining trend was observed for Σ15 PAHs in air during the 2013–2019 summer, but this was not found in soil. Potential sources of PAHs in the Fildes Peninsula were identified by PMF modeling, correlation analysis, air mass back-trajectories and component analysis. The results showed that PAHs in the gas phase were more easily influenced by long-range atmospheric transport (LRAT) than in the particle phase. Moreover, temperature played a key role in the PAHs concentration in particle phase. Occurrence of Σ15 PAHs in soil was mainly attributed to local sources including fossil fuel combustion and spilling. Graphical abstract: Unlabelled Image Highlights: This is the first analysis of PAHs sources by long-term monitoring in the Fildes Peninsula, Antarctica. Significant temperature dependence was observed on particle PAHs concentration in the west Antarctic atmosphere. Local sources, including activities with research stations and traffic, were the main PAHs contributors.